Strategi Komunikasi Perguruan Tinggi Agama Islam dalam Mendukung Internalisasi Budaya Kemahasiswaan - Zamroni, Mohammad (Jurnal Askopis, 2017)
This study aims to determine the communication strategy of Islamic religious colleges (UIN Sunan Kalijaga) in supporting the internalization of student culture, especially new students. This is qualitative research by using descriptive approach. The result of research indicate that the objective of internalization student culture in UIN Sunan Kalijaga can be guidance, mentoring, giving information, stimulation, supervision, controlling and others which in essence aim to optimize ability. Medium for delivering messages of cultural internalization student at UIN Sunan Kalijaga include; SUKA News related to student affairs, there are also a communication network, correspondance and  UIN  publication in any media. The steps in developing new students as an effort to support the internalization of student culture are: a) Dialectics and Sharing, b) Participation, c) Communication Improvement, d) Paradigm Changes, e) Priority of leading programs, Creation of conducive atmosphere, f) Assistance activities, g) Increased insight, h) Allocation of coaching fund, and i) Award presentation.Penelitian ini bertujuan untuk mengetahui strategi komunikasi perguruan tinggi agama Islam (UIN Sunan Kalijaga) dalam mendukung internalisasi budaya kemahasiswaan terutama mahasiswa baru. Ini merupakan penelitian kualitatif dengan menggunakan pendekatan deskriptif. Hasil penelitian menunjukkan bahwa tujuan internalisasi budaya mahasiswa di UIN Sunan Kalijaga dapat berupa pembinaan, pendampingan, pemberian informasi, stimulasi, pengawasan, pengendalian dan lain-lain yang pada hakekatnya bertujuan  mengoptimalkan kemampuan. Media untuk melakukan penyampaian pesan internalisasi budaya kemahasiswaan di UIN Sunan Kalijaga meliputi; Suka News berkaitan dengan kemahasiswaan, ada juga jaringan komunikasi dan juga publikasi UIN, serta surat menyurat. Langkah-langkah  dalam membina mahasiswa baru sebagai usaha dalam mendukung internalisasi budaya kemahasiswaan yaitu: a) Dialektika dan Sharing, b) Partisipasi, c) Peningkatan Komunikasi, d) Perubahan Paradigma, e) Prioritas berbagai program unggulan, Penciptaan suasana yang kondusif, f) Pendampingan kegiatan, g) Peningkatan wawasan, h) Pengalokasian dana pembinaan, dan i) Pemberian penghargaan.